1987
DOI: 10.33584/jnzg.1987.48.1772
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effects on the Germination of Herbage Legumes in New Zealand

Abstract: Percentage germination and germination rate (days to 75% germination) of 14 herbage cultivars from 5 legume species were assessed at constant temperatures of 5°, 10°, 15°, 20° and a fluctuating temperature of 5/1O°C. The percentage germination of white clover, red clover and lucerne was not affected by temperature. Germination of Woogenellup subterranean clover was reduced at 5"C, the germination of Mt Barker subterranean clover was reduced at 2O°C, and the germination of Maku lotus was reduced at 5°C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 9 publications
0
12
1
Order By: Relevance
“…5). Thus, results from this study do not substantiate the conclusion of Hampton et al (1987) that because herbage legumes germinate more rapidly than grasses "the time of sowing for seed mixtures will depend on the grass component." Implications for pasture establishment.…”
Section: Field Emergencecontrasting
confidence: 89%
See 2 more Smart Citations
“…5). Thus, results from this study do not substantiate the conclusion of Hampton et al (1987) that because herbage legumes germinate more rapidly than grasses "the time of sowing for seed mixtures will depend on the grass component." Implications for pasture establishment.…”
Section: Field Emergencecontrasting
confidence: 89%
“…For example, Charlton et al (1986) reported the number of days to germination of eight temperate grass species across a 5 to 30°C range. Similarly, Hampton et al (1987) reported the germination responses of five temperate legumes between 5 and 20°C. In most cases cultivar differences were minimal and the germination rate declined as temperature moved away from the species-specific optimum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results, and those of Skipp et al (1986), were obtained from a glasshouse maintained at around 20 o C where pots were regularly watered to avoid moisture stress. They are therefore somewhat removed from a field situation, where average 10 cm soil temperature at sowing in New Zealand in autumn and spring is from 8-14 o C depending upon location (Hampton et al, 1987), and soil moisture contents may vary considerably. Such conditions exert more stress on seeds as germination may decrease and time to emergence increase as soil temperature decreases (Charlton et al, 1986), thus potentially allowing more time for pathogen attack.…”
Section: Discussionmentioning
confidence: 99%
“…The optimum temperature range for WC germination is 20 to 30°C (Moot et al, 2000). Hampton et al (1987) reported delayed WC germination as temperatures decreased. Therefore, the slightly warmer temperatures in fall may have led to faster germination for the WC than in spring.…”
Section: Resultsmentioning
confidence: 99%